Efficient synthesis of the opioid analgesic (R)-phenampromide via an aziridinium ion - Mujahid, Mohammad; Mujumdar, Prashant; Sasikumar, Murugesan; Deshmukh, Shirish P.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2017)
A simple and efficient synthesis of the opioid analgesic agent (R)-phenampromide with high enantiopurity (> 99% ee) via the formation of an aziridinium ion as a key step using commercially available starting material is described. (C) 2017 Elsevier Ltd. All rights reserved.